Hamiltonian Chaos Beyond the KAM Theory c - Luo, Albert C. J.; Afraimovich, Valentin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
(3z(BHamiltonian Chaos Beyond the KAM Theory: Dedicated to George M. Zaslavsky (1935$1 (B2008)(3y (Bcovers the recent developments and advances in the theory and application of Hamiltonian chaos in nonlinear Hamiltonian systems. The book is dedicated to Dr. George Zaslavsky, who was one of three founders of the theory of Hamiltonian chaos. Each chapter in this book was written by well-established scientists in the field of nonlinear Hamiltonian systems. The development presented in this book goes beyond the KAM theory, and the onset and disappearance of chaos in the stochastic and resonant layers of nonlinear Hamiltonian systems are predicted analytically, instead of qualitatively. The book is intended for researchers in the field of nonlinear dynamics in mathematics, physics and engineering. Dr. Albert C.J. Luo is a Professor at Southern Illinois University Edwardsville, USA. Dr. Valentin Afraimovich is a Professor at San Luis Potosi University, Mexico.s
Stochastic and Resonant Layers in Nonlinear Hamiltonian Systems -- A New Approach to The Treatment of Separatrix Chaos and Its Applications -- Hamiltonian Chaos and Anomalous Transport in Two Dimensional Flows -- Hamiltonian Chaos with A Cold Atom in An Optical Lattice -- Using Stochastic Webs to Control The Quantum Transport of Electrons in Semiconductor Superlattices -- Chaos in Ocean Acoustic Waveguide.
Keywords: Physics; Systems theory; Vibration; Physics; Nonlinear Dynamics; Systems Theory, Control; Vibration, Dynamical Systems, Control